Improvement of Rheumatic Valvular Heart Disease in Patients Undergoing Prolonged Antibiotic Prophylaxis - Torres, Renato Pedro de Almeida; Torres, Rômulo Francisco de Almeida; Crombrugghe, Gabrielle de; Moraes da Silva, Scarllet Palacin; Cordeiro, Sarah Leticia Veroneze; Bosi, Karine Alessandra; Smeesters, Pierre R.; Torres, Rosângela Stadnick Lauth de Almeida (Frontiers in Cardiovascular Medicine, 2021)
Secondary prophylaxis of rheumatic heart diseases is efficient in reducing disease recurrence, heart damage and cardiac impairment. We aimed to monitor the clinical evolution of a large Brazilian cohort of rheumatic patients under prolonged secondary prophylaxis. From 1986 to 2018, a cohort of 593 patients with rheumatic fever were followed every six months by the Reference Center for the Control and Prevention of Rheumatic Fever and Rheumatic Cardiopathy (CPCFR), Paraná, Brazil. In this cohort, 243 (41%) patients did not present cardiac damage (group I) while 350 (59%) were diagnosed with rheumatic heart disease (RHD) (group II) using latest case definition. Among group II, 233 and 15 patients had impairment of the mitral and aortic valves respectively while 102 patients had impairment of both valves. Lesions on the mitral and aortic valves presented a regression in 69.9% and 48.7% of the patients respectively. Active patient recruitment in the reference center and early detection of oropharyngeal GAS were important factors for optimal adherence to the prophylactic treatment. Patients with disease progression were associated with non-compliance to secondary prophylaxis. No patients undergoing regular prophylaxis presented progression of the rheumatic cardiac disease. Eighteen valvular surgeries were performed and four (0,7%) patients died. This study confirmed that tailored and active efforts invested in rheumatic heart disease secondary prevention allowed for significant clinical improvement.